Carbon‐Interconnected Ge Nanocrystals as an Anode with Ultra‐Long‐Term Cyclability for Lithium Ion Batteries. (24th June 2014) - Ngo, Duc Tung; Kalubarme, Ramchandra S.; Le, Hang T. T.; Fisher, John G.; Park, Choong‐Nyeon; Kim, Il‐Doo; Park, Chan‐Jin
<x xml:space="preserve">Abstract</x> Germanium (Ge) possesses a great potential as a high‐capacity anode material for lithium ion batteries but suffers from its poor capacity retention and rate capability due to significant volume expansion by lithiation. Here, a facile synthetic route is introduced for producing nanometer‐sized Ge crystallites interconnected by carbon (GEC) via thermal decomposition of a Ge‐citrate complex followed by a calcination process in an inert atmosphere. The GEC electrode shows outstanding electrochemical performance, i.e., an almost 98.8% capacity retention of 1232 mAh g−1, even after 1000 cycles at the rate of C/2. Importantly, a high discharge capacity of 880 mAh g−1 is maintained at the very high rate of 10 C. The excellent anode performance of GEC stems from both effective buffering of carbon anchored to the Ge nanocrystals and the high open porosity of the GEC aggregated powder with an average pore diameter of 32 nm. Furthermore, the interfacial layer formed between Ge and carbon plays an essential role in prolonging the cycle life. The GEC electrode can be successfully employed as an anode for next generation lithium ion batteries.